2014
DOI: 10.1088/0004-637x/787/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Confined Partial Filament Eruption and Its Reformation Within a Stable Magnetic Flux Rope

Abstract: We present observations of a confined partial eruption of a filament on 2012 August 4, which restores its initial shape within ≈2 hr after eruption. From the Global Oscillation Network Group Hα observations, we find that the filament plasma turns into dynamic motion at around 11:20 UT from the middle part of the filament toward the northwest direction with an average speed of ≈105 km s −1. A little brightening underneath the filament possibly shows the signature of low-altitude reconnection below the filament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 51 publications
(102 reference statements)
4
29
0
Order By: Relevance
“…Photospheric magnetic cancellation (van Ballegooijen & Martens 1989) and the coronal tether-cutting reconnection (Sturrock et al 1984;Moore et al 2001) are two main mechanisms known for the buildup as well as the initial rising of sigmoid structures in the solar corona. Several studies have been performed showing the formation of sigmoid with these mechanisms (Inoue et al 2011;Liu et al 2012Liu et al , 2013Joshi et al 2014aJoshi et al , 2014bVemareddy & Zhang 2014). Other mechanisms such as torus instability (Kliem & Török 2006), kink instability (Török et al 2004), and the magnetic breakout (Antiochos et al 1999) are well known to drive the eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Photospheric magnetic cancellation (van Ballegooijen & Martens 1989) and the coronal tether-cutting reconnection (Sturrock et al 1984;Moore et al 2001) are two main mechanisms known for the buildup as well as the initial rising of sigmoid structures in the solar corona. Several studies have been performed showing the formation of sigmoid with these mechanisms (Inoue et al 2011;Liu et al 2012Liu et al , 2013Joshi et al 2014aJoshi et al , 2014bVemareddy & Zhang 2014). Other mechanisms such as torus instability (Kliem & Török 2006), kink instability (Török et al 2004), and the magnetic breakout (Antiochos et al 1999) are well known to drive the eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…It is debated whether the flux rope exists before a filament eruption or forms during the eruption. Further, there is also a class of eruptive filaments in which only a part of a filament erupts (e.g., Joshi et al 2014) or there is a failed eruption (Török & Kliem 2005). Such eruptions are modeled by simulations of partial flux rope eruptions (Gibson & Fan 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the direct observations of flux ropes in the low corona have been reported (Li and Zhang, 2013a, 2013cChen et al, 2014aChen et al, , 2014bSong et al, 2014;Joshi et al, 2014b) by using the extreme ultraviolet (EUV) data from the Atmospheric Imaging Assembly (AIA; Lemen et al, 2012) onboard the Solar Dynamics Observatory (SDO; Pesnell et al, 2012). Kumar et al (2010) presented a successive activation of magnetic flux ropes in chromospheric and EUV lines and concluded that such activation plays an important role in triggering the flare.…”
Section: Introductionmentioning
confidence: 99%